Proposed Marketing Plan for ICT-ED Institute of Science and Technology, Inc. - Jojie R. De Ramos (Education Policy and Development, 2026)
In today’s private higher education landscape, effective marketing strategies are vital for institutions to strengthen their market presence, enhance service quality, and sustain student enrollment. This study was conducted in 2024 at the ICT-ED Institute of Science and Technology, Inc., with the objective of developing a comprehensive marketing plan to improve brand positioning and support student attraction and retention. Anchored in the Segmentation, Targeting, and Positioning (STP) framework and guided by the SERVQUAL model, the study emphasizes a service-driven marketing approach that aligns promotional initiatives with quality improvement. A descriptive-quantitative research design was employed, with the sample size determined using Slovin’s formula. Using random sampling, a total of 162 respondents participated in the study, consisting of 140 students and 22 personnel. Data were collected through structured questionnaires and analyzed using Pearson’s correlation coefficient. The study demonstrates that marketing practices are strongly associated with the core dimensions of service quality, such as tangibility, assurance, responsiveness, and empathy, which indicates that effective marketing functions are a critical driver of students’ trust, perceived care, and responsiveness of institutional services. Based on these findings, a marketing plan was developed that integrates targeted promotional strategies and clearly defined marketing goals to ensure consistent messaging across market segments. The proposed plan, projected for implementation from the 2024–2025 to 2026–2027 academic years, aims to enhance stakeholder trust, reinforce student satisfaction, and strengthen ICT-ED’s competitive position in the private higher education sector.